(untitled) (Fiep Bulletin - online, 2014)
Introduction: The aging refers to a physiological process or chronological, it is a process biosocial of regression, observable in all living beings expressing themselves in the loss of capacity throughout life, due to influences of different variables. (FLECK et all, 2000). The quality of life of the elderly comprises different dimensions: environmental conditions, behavioral competence, perceived quality of life and well being subjective. Methodology: The type of study is descriptive and quasi-experimental. For the assessment of the quality of life of heart diseases not bearers of marcapasso, was used Questionnaire WHOQOL - BREF World Health Organization (WHO), for the evaluation of the quality of life of patients with marcapasso was used Questionnaire AQUAREL, a questionnaire specific evaluation of the quality of life for patients with marcapasso. Besides the IPAQ (Questionnaire International Physical Activity), a questionnaire was used to assess the profile of the way of life proposed by Nahas (2001). Results: The results of Aquarel 50% say never, 25% say they rarely and 25% from time to time feel the heart beat stronger. As the feeling of faintness, 50% said never mind, 25% rarely feel and 25% always go through that. 50% responded that never felt, 25% rarely feel and 25% almost always, feel tired and exhausted after sleeping a night of sleep. The tiredness or lack of energy has hindered or confusing you to do the daily activities, 25% responded that on occasion confuses and 75% of people say they never hurt. 50% of respondents never needed, 25% said from time to time and 25% said that almost always due to tiredness must sit or lie down during the day. The results of Whoquol were satisfactory paragraphs 6 points assessed. Conclusion: Physical activity aimed at high correlation to physical activity, the physical quality and health, according to the World Health Organization